The empire as a food utopia in Attic comedy (Circe de clásicos y modernos, 2025)
This paper attempts to argue two distinct but intertwined issues; first, that it is feasible to approach the study of ancient utopia from a perspective that uses a restricted concept of it. Second, it asserts that Athenian imperial rhetoric developed a discourse tending to idealize the empire as a guarantor of food abundance for the city, something that is satirized on the theatrical stage by Aristophanes.
Keywords: Aristophanes; comedy; Finley; Empire; utopia